PENGGUNAAN METODE KONVENSIONAL DALAM PEMBELAJARAN SENI VOKAL PADA SISWA DI INS KAYUTANAM - Yesy Gusnita; Ardipal Ardipal; Syahrel Syahrel (FBS Universitas Negeri Padang, 2012)
The purpose of this study was to describe the conventional learning methods used in studying vocal students in singing songs especially songs INS Kayutanam Minang in high school. This research is descriptive qualitative. Object of research is the use of conventional methods in the art of vocal high school students Syafei National Institute (INS). The results using conventional methods in the art of vocal INS Kayutanam high school students. Demonstration peers, kepatihan method is a special method that focuses on how to read notation numbers in Minang song, making students more quickly accept new material and easier to understand by students. Kata kunci : Metode, SMA INS, Pembelajaran, Kualitatif, Vokal